Efektivitas Penggunaan Model Pembelajaran Student Teams Achievement Division Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Zuhairina Firdaus; Erlita Umi Masytoh; Naila Amalia; Wido Rahayu Gondoarum; Fitriyah Amaliyah (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
The aim of this research is to identify whether there are differences in students' mathematical problem-solving abilities before and after the implementation of the Student Teams Achievement Divisions (STAD) Learning Model. The study was conducted on 14 fifth-grade students at SD 1 Karangmalang. Data were collected using a multiple-choice test to measure students' mathematical understanding. The research method used was a quasi-experimental design. Data analysis was performed using a paired sample t-test. The results of the study showed that the average score in the posttest was higher compared to the average score in the pretest, indicating an improvement in students' mathematical problem-solving abilities after the implementation of the STAD learning model. Furthermore, the research results also showed that the obtained significance value was 0.000, which is smaller than 0.05. Therefore, the null hypothesis (Ho) is rejected. This indicates that there is a significant difference between the mathematical problem-solving abilities before and after the use of the STAD learning model